2021
DOI: 10.1108/edi-05-2020-0132
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement and commitment to two Australian autism employment programs: associations with workload and perceived supervisor support

Abstract: PurposeAlthough there is growing academic and business interest in autism employment programs, few studies have examined employee (manager and coworker) attitudes toward these programs. The purpose of this study is to examine the impact of workload changes (a job demand) and perceived supervisor support (a job resource) on commitment to the program and employee engagement more broadly.Design/methodology/approachA total of 229 employees from two Australian public sector organizations completed a survey about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Data collated as part of this study raises some important questions for future research. Retention rates during the program and employment outcomes achieved post completion of the program, as well as the success of some individuals in finding unassisted employment opportunities prior to completing the program, support the view that autistic people can be successful and productive employees, provided appropriate workplace supports are in place (Krzeminska et al, 2019;Nicholas et al, 2015;Spoor, Flower, et al, 2021). Research is needed to better understand the supports that might be needed as autistic people progress through different employment stages (e.g.…”
Section: Future Directionsmentioning
confidence: 85%
“…Data collated as part of this study raises some important questions for future research. Retention rates during the program and employment outcomes achieved post completion of the program, as well as the success of some individuals in finding unassisted employment opportunities prior to completing the program, support the view that autistic people can be successful and productive employees, provided appropriate workplace supports are in place (Krzeminska et al, 2019;Nicholas et al, 2015;Spoor, Flower, et al, 2021). Research is needed to better understand the supports that might be needed as autistic people progress through different employment stages (e.g.…”
Section: Future Directionsmentioning
confidence: 85%
“…This is compounded when managers must consider how fostering an inclusive environment can require adjusting their neurotypical subordinates’ job demands, potentially influencing neurotypical employees’ attitudes toward inclusion efforts. Spoor and colleagues (2021) found that perceived workload changes associated with implementing autism employment programs affected coworker attitudes toward the programs (i.e., perceived workload increases were linked to coworkers’ lower affective commitment, but higher continuance commitment, toward the program). These findings suggest that managers need to proactively manage perceived demands of neurodiversity inclusion initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if organizations are serious about having a neurodiverse workforce, "they may need to reconfigure staffing levels, workload assignments, and 'traditional' job duties in ways that better equip employees with the energy needed to do the work necessary for fostering inclusive workplaces" (Gabriel et al, 2022;227). Although autism-specific adaptations and refinements are needed, frameworks popular in the management literature, such as the job-demands resources model (Bakker & Demerouti, 2007), may serve as powerful tools for identifying pathways through which job demands can be reduced and resources increased for managers, members of neurodivergent groups, and their colleagues (Spoor et al, 2021). To this end, assistive devices (e.g., iPads) and apps may lessen demands on managers, because they can reduce the need for support (e.g., coaching) from others (Gentry et al, 2015;Khalifa et al, 2020).…”
Section: Recommendations For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…autism knowledge) and organisational benefits (e.g. organisational reputation, organisational pride; Grenawalt et al, 2020 ; Spoor, Bury, et al, 2021 ) to such programmes, but they have also reported challenges associated with perceived workload concerns and their engagement with these programmes ( Spoor, Flower et al, 2021 ), and concerns regarding integration beyond the programme ( Spoor, Bury, et al, 2021 ), but not in all studies ( Grenawalt et al, 2020 ). While these studies report facilitators and barriers at the individual or co-worker level, very little research has considered the broader organisation at the ecosystem level within autism employment ( Vogus & Taylor, 2018 ).…”
mentioning
confidence: 99%